Analisis Kepuasan Mahasiswi Terhadap Fasilitas Asrama Putri Universitas Quality - Nilam Sari; Herdina Simbolon; Nurlita Apriliani; Anisa Padla; Sheva utari; Yemima Yemima (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This study aims to analyze the level of female student satisfaction with the female dormitory at Quality University. Female students here are users of the female dormitory at Quality University. Student satisfaction is an important factor in supporting the welfare and comfort of dormitory residents, which can affect female students' academic achievement and daily life. This research method uses descriptive analysis techniques with survey methods, where data is obtained through questionnaires distributed to 67 female dormitory residents. Data collection analysis was carried out using a Likert scale to measure student perceptions of various aspects of facilities, such as rooms, cleanliness, security and other public facilities. The results of the study showed that overall respondents' assessments of the female dormitory facilities were: those who stated that they were very satisfied were 20.5%, satisfied 36.8%, quite satisfied 22.6% and less satisfied 20%. Thus, for satisfied and very satisfied if totaled 57.3%, and this is categorized as quite satisfactory. The greatest dissatisfaction of respondents was related to cleanliness and public services. Although the average respondent assessment was quite satisfactory, there were several aspects that needed to be improved, especially regarding cleanliness and related facilities. Recommendations for improvement are given to improve the quality of services at the girls' dormitory in the future.